Resuscitating the wage channel in models with unemployment fluctuations - Kai Christoffel; Keith Kuester (European Central Bank (ECB), 2008)
All else equal, higher wages translate into higher inflation. More rigid wages imply a weaker response of inflation to shocks. This view of the wage channel is deeply entrenched in central banks' views and models of their economies. In this paper, we present a model with equilibrium unemployment which has three distinctive properties. First, using a search and matching model with right-to-manage wage bargaining, a proper wage channel obtains. Second, accounting for fixed costs associated with maintaining an existing job greatly magnifies profit fluctuations for any given degree of wage fluctuations, which allows the model to reproduce the fluctuations of unemployment over the business cycle. And third, the model implies a reasonable elasticity of steady state unemployment with respect to changes in benefits. The calibration of the model implies low profits, but does not require a small gap between the value of working and the value of unemployment for the worker.
Keywords: E31; E32; E24; J64; 330; business cycle; E24; E32; J64; JEL Classification System: E31; Keywords: Bargaining; real rigidities; Unemployment; Verhandlungstheorie des Lohnes; Arbeitslosigkeit; Lohnrigidität; Inflationsrate; Konjunktur; Theorie